1999
DOI: 10.1590/s0301-80591999000400010
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of culture supernatants from Bacillus thuringiensis Berliner strains against Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) larvae

Abstract: Novel vegetative insecticidal proteins (Vips) identified in the supernatant of Bacillus thuringiensis (B.t.) cultures have shown to provide adequate control over a wide spectrum of economically important crop pests. To evaluate the potential applicability of these proteins against fall armyworm (Spodoptera frugiperda Smith) larvae, the most important insect pest for tropical maize, the characteristics and mortality effects of culture supernatants from five B.t. strains were investigated. Striking differences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 13 publications
(17 reference statements)
0
23
0
4
Order By: Relevance
“…Among the latter are "Vip" proteins, in which the "Vip3A" is important due to its toxic effects on Lepidoptera, including S. frugiperda (Schnepf et al 1998;De Maagd et al 2003). Testing five-strain supernatant of B. thuringiensis against the fall armyworm, Barreto et al (1999) found mortality between 65-90 % caused by "Vip" proteins. Thus, mortality due to the bacteria could be higher than that due to Cry proteins alone.…”
Section: Resultsmentioning
confidence: 99%
“…Among the latter are "Vip" proteins, in which the "Vip3A" is important due to its toxic effects on Lepidoptera, including S. frugiperda (Schnepf et al 1998;De Maagd et al 2003). Testing five-strain supernatant of B. thuringiensis against the fall armyworm, Barreto et al (1999) found mortality between 65-90 % caused by "Vip" proteins. Thus, mortality due to the bacteria could be higher than that due to Cry proteins alone.…”
Section: Resultsmentioning
confidence: 99%
“…No entanto, em seu trabalho, os autores observaram genes lepidóptero-específicos em porcentagem muito maiores do que a de coleóptero-específicos, o oposto do que ocorreu nesse trabalho, cuja porcentagem de isolados coleóptero-específicos (22,37%) foi ligeiramente maior em relação aos lepidóptero-específicos (11,8%). A presença de genes efetivos contra larvas pertencentes à ordem Coleoptera não é tão comum quanto à presença de genes efetivos contra a ordem Lepidoptera; em alguns trabalhos não se observou nenhum isolado portando genes codificadores de proteínas efetivas a larvas da ordem Coleoptera (Chak et al, 1994;Ben-Dov et al, 1997). Esse resultado mais uma vez infere o perfil distinto dos isolados deste conjunto avaliado.…”
Section: Resultados E Discussão Caracterização Molecularunclassified
“…O perfil distinto de genes da classe cry1 verificado nesse trabalho reforça essa hipótese. Assim como observado dentro da classe cry1, as diferenças observadas para as frequências de genes cry entre as outras famílias de genes também são dependentes da fonte de origem e da área geográfica onde as amostras foram coletadas (Ben-Dov et al, 1997;Bravo et al, 1998).…”
Section: Resultados E Discussão Caracterização Molecularunclassified
See 2 more Smart Citations